Modified Maxillary-Swing Approach for Resection of Primary Malignancies in the Pterygopalatine Fossa - Xie, Li; Huang, Wenxiao; Wang, Junqi; Zhou, Yue; Chen, Jie; Chen, Xue (Frontiers in Oncology, 2020)
Background En bloc resection of malignancies in the pterygopalatine fossa poses critical challenges. Using the modified maxillary swing (MMS) approach we achieve monobloc removal of primary malignancies in this region. The surgical techniques and indications are discussed in details. Methods Seven patients with primary malignancies in the pterygopalatine fossa were enrolled in this retrospective study from Jan 2012 to Jan 2019. After the malignancies proven by biopsy and evaluation with CT and MRI scan, all patients received the MMS approach for extirpation of the malignant tumors in the pterygopalatine fossa under general anesthesia. Regular follow-up was carried out with CT and MRI scan postoperatively. Results En bloc resection was successfully performed in all cases. Negative margins were observed in 6 cases and positive margins were found in one patients with adenoid cystic carcinoma who received postoperative radiotherapy. The most common complication was facial numbness. During the follow-up period (range, 6 to 69 months), one patients suffered from recurrence while others did not. Conclusions The advantages of the MMS include wide surgical field, full exposure and easy manipulation. The MMS approach is expected to become an alternative for monobloc resection of malignancies in the pterygopalatine fossa with the involvement of infratemporal fossa, maxillary sinus, nasal cavity, orbit or oral cavity.